The expression and clinical value of LRP11, FUBP1 and TET1 in cervical cancer: Expression of genes effective in cervical cancer - Zhao, Xiaojie; Li, Suhua; Wen, Jiexin; Li, Yawei (Cellular and Molecular Biology, 2023)
Cervical cancer is the second leading cause of cancer death among women worldwide. Identification of effective genes along with biological markers as targeting agents is very necessary for the diagnosis and treatment of this disease. Bioinformatics techniques along with genetic and molecular investigations have provided the possibility of studying different levels of information such as the genome, transcriptome, proteome, and metabolize with high depth and accuracy. The collection of these data provides comprehensive and valuable information about the investigated phenotypes, including complex diseases such as cancer. In this study, we examined three genes LRP11, FUBP1, and TET1 related to cervical cancer. The results of this study showed that the level of expression of these genes is high in lymph nodes and the thyroid and is less in the pancreas and liver. Also, the expression level of the FUBP1 gene is higher than that of LRP11, and the expression level of the LRP11 gene is higher than that of TET1. Regarding the structure and proteomics of the studied genes, it can be seen that due to the presence of more domains in the LRP11 and FUBP1 genes, these genes probably independently participate in various functions and have a wider range of activity than the TET1 gene. Also, the analysis of the stability of the examined genes showed that the stability of the FUBP1 gene is relatively higher than that of the TET1 gene, and this gene is also more stable than the LRP11 gene. Considering that these genes are effective key genes for the early detection of cervical cancer, it is hoped that they will be used as markers in the diagnosis and treatment of cervical cancer.